Pengaruh Kebijakan Dividen, Leverage dan Good Corporate Governance Terhadap Nilai Perusahaan pada Perusahaan Perkebunan Yang Terdaftar Di Bursa Efek Indonesia - Dwi Zahara (UNIVERSITAS DHARMAWANGSA, 2026)
This study aims to analyze the effect of dividend policy, leverage, and Good Corporate Governance (GCG) on firm value in plantation companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. Firm value is measured using Price to Book Value (PBV), dividend policy using Dividend Payout Ratio (DPR), leverage using Debt to Equity Ratio (DER), and GCG using the proportion of independent commissioners. The study employs a quantitative descriptive approach with secondary data from annual reports. A sample of 8 plantation companies was selected through purposive sampling from 30 companies, resulting in 40 observations. Panel data multiple linear regression with the Random Effect Model was applied using EViews 12. Results show that partially, dividend policy has no significant effect on firm value, leverage has a positive and significant effect, while GCG has no significant effect. Simultaneously, the three variables do not significantly affect firm value.